Analysis of biological materials by the atomic absorption spectrophotometry. I. Determination of total copper, iron and zinc in chicken livers - Guimarães, Jorge Almeida; Garcia, Eloi de Souza; Ubatuba, Fernando Braga (Pesquisa Agropecuaria Brasileira, 2014)
Total copper, iron and zinc contents of male Shaver-Starbro pullet chicken livers were determined by atomic absorption spectrophotometry. In applying this method to dry ashed samples of liver tissue from 32 normal animals (1,34 mean body weight) the following values were obtained: 14,4 ± 0,85 for copper, 283,3 ± 19,78 for iron and 130,4 ± 4,21 for zinc (mean ± standard deviation ppm refered to tissue dry weight). Recovery tests were carried out to check the occurrence of metal interferences and contamination as well as analytical losses. Very good recoveries were obtained both in the absence of organic matter (101,3% for Cu, 102,9% for Fe and 99,0% for Zn) and in the presence of chicken powder (92,9% for Cu, 97,7% for Fe and 98,0% por Zn). The results of these tests excluded the eventual contamination of the samples, glassware and reagents used. There were no evidences of any spectral interference by other elements normally present in large amounts in the ashes, such as, sodium, potassium, calcium and phosphorus. Duplicate error of analysis indicated the good reproducibility of the method. Atomic absorption spectrophotometry quantitative analysis of the metalic elements occurring in animal tissues and body fluids is recommended in view of its sensitivity, versatility and convenience. The advantages have been emphasized particularly for surveys on trace elements deficiences occurring in bovine and other animal species, which requires a convenient handling of large number of samples. The method offers, even so, the advantage of a direct analytical tool, free of troublesome and time consuming fractionation steps. The simplicity of the procedure and the reproducibility and reliability of the results obtained lead to the adaption of this method for analytical studies of bovine and avian mineral metabolism undertaken in this laboratory.